Longitudinal hematological change in uncomplicated twin pregnancies: The white blood cell count decreases through pregnancy after the first trimester - Masaki Sekiguchi; Jin Muromoto; Kohei Ogawa; Katsusuke Ozawa; Naoyuki Miyasaka; Haruhiko Sago (Elsevier, 2024)
Objective: Longitudinal hematological changes throughout twin pregnancies have not been reported. This study aimed to reveal longitudinal changes in hematological indices in twin pregnancies. Materials and methods: We conducted a retrospective chart review of hematological changes in uncomplicated twin pregnancies delivered at ≥37 weeks of gestation between 2010 and 2013 and randomly selected uncomplicated singletons during the same period. A complete blood count and hemogram were performed as blood examinations in the first trimester (9-13 weeks), late second trimester (22-27 weeks), mid-third trimester (33-35 weeks, only in twin pregnancies), and late third trimester (36-38 weeks). We evaluated inter-trimester differences in hematological indices and compared the values between twin and singleton pregnancies in each trimester. Results: The final analysis group included 60 twin pregnancies and 63 singleton pregnancies. The white blood cell (WBC) count in twin pregnancies decreased throughout the pregnancy after the first trimester and became significantly lower than that in singletons in the late third trimester. The WBC count showed only a slight decrease in the third trimester in singleton pregnancies, whereas it showed a marked decrease throughout the pregnancy in twin pregnancies. The marked decrease in the total WBC count in twin pregnancies is mainly due to a decrease in neutrophils. The red blood cell count and hemoglobin and hematocrit values in twin pregnancies showed more marked decreases in the second trimester than in singletons. No decrease was observed after the second trimester of pregnancy. The platelet count decreased in the third trimester of twin pregnancies. Conclusion: We clarified the longitudinal hematological changes in twin pregnancies that showed augmentation of or differed from those of singleton pregnancies. It should be specifically mentioned that the WBC count markedly decreased through pregnancy after the first trimester, which is a characteristic change in twin pregnancies.